IDNLearn.com makes it easy to get reliable answers from knowledgeable individuals. Our experts provide prompt and accurate answers to help you make informed decisions on any topic.

Solve: 3n - 6 = -8(6 +5n)
and explain how to solve it


Sagot :

Answer:

Step-by-step explanation:

First use distributive property: a(b + c) = a*b + a*c

3n - 6 = -8(6 + 5n)

3n - 6 = 6 * (-8) + 5n *(-8)

3n - 6 = -48 - 40n

Now add 40n to both sides

3n - 6 + 40n = -48 - 40n + 40n

43n - 6 = -48

Now add 6 to both sides

43n - 6 + 6 = -48 + 6

           43n = -42

               n = -42 /43

Answer:

0.98

Step-by-step explanation:

3n-6=-8(6+5n)

3n-6=-48-40n

3n=-48-40n+6

40n+3n=-42

43n=-42

n=0.98 (I rounded it)

We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com provides the answers you need. Thank you for visiting, and see you next time for more valuable insights.